Action collective et gestion sanitaire des élevages porcins en Corse - Marie Gisclard; Perrine Devleeshouwer; François Charrier; François Casabianca (Développement Durable et Territoires)
The new health governance in France asks producers organizations to take part in decision-making regarding animal health. The hog farming sector in Corsica has recently organized itself through organizations aiming at economic integration. Yet the organizations do not represent the whole sector. The article sheds light on other forms of collective action regarding two animal health management features : territorially based discreet collective actions.